Detrital zircon analysis from the Neoproterozoic-Cambrian sedimentary cover (Cuyania terrane), Sierra de Pie de Palo, Argentina: Evidence of a rift and passive margin system? - Naipauer, Maximiliano (2010)
Metamorphic basement and its Neoproterozoic to Cambrian cover exposed in the Sierra de Pie de Palo, a basement block of the Sierras Pampeanas in Argentina, lie within the Cuyania terrane. Detrital zircon analysis of the cover sequence which includes, in ascending order, the El Quemado, La Paz, El Desecho, and Angacos Formations of the Caucete Group indicate a Laurentian origin for the Cuyania terrane. The lower section represented by the El Quemado and La Paz Formations is interpreted as having an igneous source related to a rift setting similar to that envisioned for the southern and eastern margins of Laurentia at approximately 550 Ma. The younger strata of the El Desecho Formation are correlative with the Cerro Totora Formation of the Precordillera, and both are products of rift sedimentation. Finally, the Angacos Formation and the correlative La Laja Formation of the Precordillera were deposited on the passive margin developed on the Cuyania terrane. The maximum depositional ages for the Caucete Group include ca. 550 Ma for the El Quemado Formation and ca. 531 Ma for the El Desecho Formation. Four different sediment sources areas were interpreted in the provenance analysis. The main source is crystalline basement dominated by early Mesoproterozoic igneous rocks related to the Granite-Rhyolite province of central and eastern Laurentia. Possible source areas for 1600 Ma metamorphic detrital zircons of the Caucete Group include the Yavapai-Mazatzal province (ca. 1800–1600 Ma) of south-central to southwestern Laurentia. Younger Mesoproterozoic zircon is likely derived from Grenville-age medium- to high-grade metamorphic rocks and subordinate igneous rocks that form the basement of Cuyania as well as the southern Grenville province of Laurentia itself. Finally, Neoproterozoic igneous zircon in the Caucete Group records different magmatic pulses along the southern Laurentian margin during opening of Iapetus and break-up of Rodinia. Northwestern Cuyania terrane includes a small basement component derived from the Granite- Rhyolite province of Laurentia, which was the source for detrital zircons found in the middle Cambrian passive margin sediments of Cuyania.